2000
DOI: 10.1097/00004836-200007000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection in Argentina

Abstract: Our aim was to assess the prevalence of Helicobacter pylori (Hp) infection in Argentina, in the general population and by age groups, and to determine the value of various epidemiologic variables as predictors of Hp infection. The study comprised 754 subjects (443 women 158.7%], 311 men [41.3%]) from both genders, consecutively recruited from health centers where patients were undergoing routine medical analyses. Average age was 32 +/- 22 years. The pediatric group included subjects < or =18 years of age (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 15 publications
1
17
0
4
Order By: Relevance
“…Several reports included individuals from infancy through old age, but did not report the proportion of the study population that was young children (e.g., ≤age 5 years) (Mitchell et al 1992 a , b ; Teh et al 1994). Other studies focused on children and teenagers (≤20 years), but again provided no details on the distribution of age groups (Klein et al 1991; Begue et al 1998; Olmos et al 2000). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports included individuals from infancy through old age, but did not report the proportion of the study population that was young children (e.g., ≤age 5 years) (Mitchell et al 1992 a , b ; Teh et al 1994). Other studies focused on children and teenagers (≤20 years), but again provided no details on the distribution of age groups (Klein et al 1991; Begue et al 1998; Olmos et al 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Effects on H. pylori associated with the frequency of access to a sanitary sewerage system has been evaluated in several studies (Oliveira et al 1994; Katz et al 1997; Souto et al 1998; Redlinger et al 1999; Olmos et al 2000). These studies have reported inconclusive or minimal differences in prevalence of infection between children with and without access to a sewer network.…”
Section: Discussionmentioning
confidence: 99%
“…49, Nos. 11/12 (November/December 2004) In Argentina high rates of H. pylori infection are related to poor social and economic conditions, low levels of education, and older age, with the highest frequency in the fifth decade of life (9,10). Since HIV-infected and non-HIV-infected individuals assisted at our hospital come from the same urban area and belong to the same social class, we only had to match them according to age to demonstrate that the prevalence of H. pylori infection was equivalent in both groups, regardless of the HIV condition.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence has been reported in people who have been in institutions such as orphanages or residences for the elderly, something we were unable to confirm (35,36). Some studies demonstrated higher prevalence rates in individuals who shared a bedroom or bed during childhood, while others failed to find any such association (6,10,21,(37)(38)(39)(40). In this case, the univariate analysis showed that sharing a bedroom or bed during childhood had a direct association or large trend towards increased prevalence, respectively.…”
Section: Discussionmentioning
confidence: 76%